PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP STRUKTUR MODAL : ANALISIS KOMPARATIF PADA INDUSTRI PAKAN TERNAK DAN INDUSTRI SEMEN DI BURSA EFEK INDONESIA (2001-2007) - Priyo Darmawan (Universitas Bunda Mulia, 2017)
Financial function is one of the important function in company activities. Therefore, it be might be managed properly by each company, especially, dealt with its capital structure. This study considers the significance of the determinants of capital structure on a sample of Animal Feed Manufacturers and Cement Manufacturers which are public listed firms at the Jakarta Stock Exchange from 2001 – 2007. The result of this investigation shows that firms have impact variables of firm characteristics which effect the capital structure are business risk, profitability and assets structure (tangibility), and earning volatility. Also, this study investigates among the variables which are the most dominated variables on capital structure. Keywords : business risk, profitability, assets structure, debt to total assets, earning volatility, firm size, and capital structure, irrelevant and relevant capital structure theories